Deficiency of slow skeletal muscle troponin T causes atrophy of type I slow fibres and decreases tolerance to fatigue - Wei, Bin (Blackwell publishing Ltd, 2014)
The total loss of slow skeletal muscle troponin T (ssTnT encoded by TNNT1 gene) due to a nonsense mutation in codon Glu(180) causes a lethal form of recessively inherited nemaline myopathy (Amish nemaline myopathy, ANM). To investigate the pathogenesis and muscle pathophysiology of ANM, we studied the phenotypes of partial and total loss of ssTnT in Tnnt1 gene targeted mice. An insertion of neomycin resistance cassette in intron 10 of Tnnt1 gene caused an approximately 60% decrease in ssTnT protein expression whereas cre-loxP-mediated deletion of exons 11–13 resulted in total loss of ssTnT, as seen in ANM muscles. In diaphragm and soleus muscles of the knockdown and knockout mouse models, we demonstrated that ssTnT deficiency resulted in significantly decreased levels of other slow fibre-specific myofilament proteins whereas fast fibre-specific myofilament proteins were increased correspondingly. Immunohistochemical studies revealed that ssTnT deficiency produced significantly smaller type I slow fibres and compensatory growth of type II fast fibres. Along with the slow fibre atrophy and the changes in myofilament protein isoform contents, ssTnT deficiency significantly reduced the tolerance to fatigue in soleus muscle. ssTnT-deficient soleus muscle also contains significant numbers of small-sized central nuclei type I fibres, indicating active regeneration. The data provide strong support for the essential role of ssTnT in skeletal muscle function and the causal effect of its loss in the pathology of ANM. This observation further supports the hypothesis that the function of slow fibres can be restored in ANM patients if a therapeutic supplement of ssTnT is achieved.